THE USE OF TREASURE HUNT GAME TOWARD THE STUDENTS’ VOCABULARY MASTERY AT ISLAMIC SENIOR HIGH SCHOOL - Nurpatima Nurpatima; Kamsinah Kamsinah; St Nurjannah YT (Universitas islam Negeri Alauddin Makassar, 2020)
The researcher aims to find out the effectiveness using Treasure Hunt Game toward students’ vocabulary mastery with the research objectives: to find out the use of Treasure Hunt Gametowardthe first grade students’ vocabulary mastery at Islamic Senior High School of Muhammadiyah Palampang. This research was conducted at the class X MIA 1 and X MIA 2. The sample of this research was 50 students from 280 populations. The controled class was took from class X MIA 1, while the experimental class was from X MIA 2. The number of the sample in each class was 25 students.Quasi experimental design was applied in this research with two group pre-test and post-test design. The instrument used to collect data was vocabulary test.Research findings showed that the experimental class got score on pre-test with the mean score 44,2. After giving treatment the students got change, they got score with the mean score 59,9. The result of the data analysis indicated that there was a change of the students’ vocabulary mastery after being taught using Treasure Hunt Game. It was proved by the result of the statistical analysis of the level significance P = 0.05 with degree of freedom (df) = 48 indicated that the t-test values of the students’ vocabulary mastery (2,53) was higher than the t-table (2,01). Based on the result of analysis, the researcher concludes that using Treasure Hunt Game was effective toward the students’ vocabulary mastery at the first grade students of Islamic Senior High School of Muhammadiyah Palampang, because Treasure Hunt Game give a lot of fun, the students enjoy the learning without any preasure. Than, Treasure Hunt Game stimulates students engagement in learning process. If students enjoy the learning process, they were enthusiastic enough to involve and compete each other in learning process.Keywords: Treasure Hunt Game, Vocabulary mastery, First Grade Students